2015
DOI: 10.1371/journal.pone.0116085
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Total Factor Productivity of Cotton Production in Egypt

Abstract: The main objective of this paper is to decompose the productivity growth of Egyptian cotton production. We employ the stochastic frontier approach and decompose the changes in total factor productivity (CTFP) growth into four components: technical progress (TP), changes in scale component (CSC), changes in allocative efficiency (CAE), and changes in technical efficiency (CTE). Considering a situation of scarce statistical information, we propose four alternative empirical models, with the purpose of looking fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Rahman and Barmon (2018) reported that the total factor energy productivity was mainly driven by the technological progress of the gher farming system in Bangladesh. Hossain et al (2012) reported that technological change was the main driving force for the improvement of TFP of rice in Bangladesh, whereas Rodriguez and Elasraag (2015) reported that the technological change negatively contributes to the TFP growth. It can be argued that the upward shift in technological progress is the result of diffusion of Green Revolution (GR) technology and other factors, such as significant increase in use of chemical fertilizer, extended the irrigated area, infrastructural development, research and extension expenditure, farmers' accessibility to high yielding varieties (HYV) of seed, and availability of market information.…”
Section: Growth In Tfp and Its Components By Regionmentioning
confidence: 99%
“…Rahman and Barmon (2018) reported that the total factor energy productivity was mainly driven by the technological progress of the gher farming system in Bangladesh. Hossain et al (2012) reported that technological change was the main driving force for the improvement of TFP of rice in Bangladesh, whereas Rodriguez and Elasraag (2015) reported that the technological change negatively contributes to the TFP growth. It can be argued that the upward shift in technological progress is the result of diffusion of Green Revolution (GR) technology and other factors, such as significant increase in use of chemical fertilizer, extended the irrigated area, infrastructural development, research and extension expenditure, farmers' accessibility to high yielding varieties (HYV) of seed, and availability of market information.…”
Section: Growth In Tfp and Its Components By Regionmentioning
confidence: 99%
“…All four variables increased when TFP was increased.So, it is clear that they are a significant growth source in cocoa farming in the Central Sulawesi. The ED, EA, FE, and SN may likewise affect the technical inefficiency of cocoa farming, influencing productivity growth (Effendy et al, 2013b;Rinaldi et al, 2013;Rodríguez and Elasraag, 2015).…”
Section: The Factors That Affect Tfp Variation In Cocoa Farmingmentioning
confidence: 99%
“…Effendy et al (2013b) and Rinaldi et al (2013) have shown the technical efficiency of cocoa farming ranges from 0.3 to 0.9, meaning there is still inefficiency in cocoa farming. If there is inefficiency, it is necessary to consider its effect on productivity growth (Rodríguez and Elasraag, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many agro-industrial units using the latest techniques have been established, meeting world quality standards and capable of accessing several foreign markets. It is A literature review of the TFP growth in the Egyptian agricultural sector reveals that empirical studies were focusing on analyzing TFP of specific agricultural commodities (Rodriguez & Elasraag 2015;Abou-Saad, 2012;Bahloul, 1999). Rodriguez and Elasraag (2015), decomposed the productivity growth of Egyptian cotton production using stochastic frontier approach, and were tracking the changes of the TFP composition over the period 1990-2008.…”
Section: Overview Of the Agricultural Sector And Its Tfp Growth In Egyptmentioning
confidence: 99%